A comparison of two techniques of cell block preparation - Kasichhwa, Anita; Shrivastav, Shreya; Agrawal, Ayushi (Journal of Pathology of Nepal, 2019)
Background: Cell block technique is a method of preparing cytological material so that it can be processed, sectioned, stained, and viewed as a histology section. The study compared two methods of cell block preparation, plasma-thromboplastin method and collodion bag technique of cell block preparation. Materials and Methods: Samples were randomly processed by plasma-thromboplastin technique or by collodion bag technique. Hematoxylin/Eosin stained cell block sections were examined and scored scaling from 1 to 3 for cellularity, clarity, nuclear features, cytoplasm, use of ancillary test and recovery of cell-cluster and fragments. Mann-Whitney U test was used for comparing two methods and establishing statistical significance. Results: The median cellularity score was 2.0 for plasma-thromboplastin and 1.0 for collodion bag. The median morphological preservation score and use of ancillary test score were 2.0 for both of the method while median score for recovery of cell cluster and fragments was 2.0 for collodion bag and 1.0 for plasma-thromboplastin. Statistically, both of the methods had similar results in cell block quality. The median total score for plasma-thromboplastin and collodion bag were 10.0 and 11.0 respectively. Diagnostic cell blocks were obtained in 46.51% of cell block by plasma-thromboplastin method and 60.52% of cell block by collodion bag method improving the diagnosis over conventional smear in 76.74% and 81.57% respectively. Conclusions: Cell block by plasma-thromboplastin and collodion bag method are cost effective, useful adjunct to FNA for diagnosis of mass lesion. Both techniques has no significant difference in quality of cell block produced.